Perbedaan Pengetahuan Siswa Tentang Penyakit Hepatitis A Sebelum Dan Sesudah Penyuluhan Di MTsN 02 Bondowoso Tahun 2015 - Putri Megasari (Akademi Keperawatan Dharma Husada Kediri, 2016)
Hepatitis has become a health problem in the world. The hepatitis virus infected many people. According to the teacher of MTsN 02 Bondowoso more than 20 students have hepatitis A viral infection. The purpose of this research was to know the differences of students' knowledge about hepatitis A before and after counseling in MTsN 02 Bondowoso 2015. This study used pre-experimental (pre-post test design). This study used stratified random sampling technique, 127 students from 270 sample involved this research,and 143 students was excluded. We used questionnaires to collect data. The results showed that the mean value of the students 'knowledge about hepatitis A before counseling in MTsN 02 Bondowoso 2015 was 83.96 with the lowest value of 37.5 and the highest value was 100. The mean value of the students' knowledge about hepatitis A after counseling in MTsN 02 Bondowoso 2015 was 93.21 with the lowest value waf 62.5 and the highest value was 100. Paired t test showed that t (-9.07) > t table (1.98), the null hypothesis (H0) was rejected. There was a difference between students' knowledge about hepatitis A before and after counseling in MTsN 02 Bondowoso 2015. This study showed that routine counseling by healthcare provider was important to prevent hepatitis A infection. Keywords: counseling, knowledge of students, hepatitis